Chilly climate perceived by female engineering undergraduates: an exploratory study using concept mapping - Kim, Tanhui; Kim, Dongil (Frontiers in Psychology, 2023)
The purpose of this study was to explore the chilly campus climate perceived by female undergraduate engineering students in South Korea using the concept mapping method. Semi-structured interviews were conducted with 13 participants enrolled for more than four semesters at four-year coeducational universities. Fifty-two statements were extracted under the following four clusters: i) “Exclusion and alienation inherent in the culture,” ii) “Sexual objectification and lack of gender sensitivity,” iii) “Male-centered academic situations,” and iv) “Prejudice and generalization.” This study is significant because it conceptualizes the subjective experience of minorities in a collegiate environment and provides influence rating results for prioritized measures. Our findings will be helpful in formulating educational policies, psychological counselling, and social advocacy activities. Future research should target larger populations, and cover more diverse cultures, majors, and age groups.